Fenomena Pergeseran Makna Akibat Viralitas pada Film Budi Pekerti (Analisis Semiotika Roland Barthes) - Raisha Fatiha; Laila Rohani (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2026)
Film, as a medium of mass communication, not only provides entertainment but also represents social phenomena, including the transformation of meaning in the era of social media virality. Viral circulation often detaches information from its original context, allowing meanings to be reconstructed through framing, selective dissemination, and public interpretation. This study examines how shifts in meaning caused by virality are represented in Wregas Bhanuteja’s Budi Pekerti and explores the ideological implications embedded in the process. Using a qualitative approach and Roland Barthes’ semiotic framework, the study analyzes seven selected scenes through the levels of denotation, connotation, and myth. Data were collected from dialogues, character expressions, visual symbols, and narrative situations related to social media virality. The findings reveal that virality functions not merely as a mechanism for information dissemination but as a process of symbolic reconstruction that transforms partial representations into socially accepted “truths.” At the mythological level, the film naturalizes the belief that visibility and repetition in digital media are indicators of credibility, regardless of contextual accuracy. The study’s novelty lies in demonstrating how virality operates as a semiotic mechanism that produces and legitimizes new meanings, thereby shaping public perception, social judgment, and digital reality in contemporary society.